Labour analgesia: awareness and barriers among healthcare providers at a tertiary care centre - Sangineni, Kalyani S. D. L.; Salian, Sushmitha; Waghray, Anish; Garre, Sandeep; Chikkala, Rama Krishna Prasad; Ayya, Syama Sundar (International Journal of Research in Medical Sciences, 2026)
Background: Labour analgesia has evolved from use of ether to modern regional techniques, significantly improving maternal and neonatal outcomes. Despite advancements and increasing awareness utilization remains limited among parturients in India. The aim of the study was to assess knowledge, perceptions of healthcare providers regarding labour analgesia and to identify barriers to its wider implementation. Methods: Mixed-method cross-sectional survey was conducted among 303 healthcare providers at our institute using a validated questionnaire. Both qualitative and quantitative data were collected. Internal consistency and face validity were established during pilot testing. Descriptive and inferential analysis were performed. Results: Of 303 respondents, 60.7% (185) were female and 46.2% (139) were doctors. Although 95% (285) were aware of the term labour analgesia, only 52.8% (161) had witnessed its administration. Approximately one quarter of respondents believed it prolongs the duration of labour. Barriers to utilization of labour analgesia included lack of availability of anaesthesiologist (14.2%, n=42) and not being offered services (17.8%, n=55). A majority (68.3%, n=207) endorsed antenatal education, and 56.1% (n=170) supported its inclusion in government hospitals. Conclusions: Despite high awareness of labour analgesia, its utilization remains limited due to systemic barriers. Increased training and practice of labour analgesia in teaching institutes may help build trust and enhance its utilization.